Factors affecting stock price (KLCI) in Malaysia / Muhammad Rifaei Ibrahim - Ibrahim, Muhammad Rifaei (Faculty of Business and Management, 2020)
This chapter provides an overview of this research topic relating to Bursa Malaysia macroeconomic variables and stock prices (KLCI), and addresses research issue statements leading to research goals of the report and ultimately research questions. The objective of this research is to investigate the relation between macroeconomic variables such as inflation, interest rate, exchange rate, and gross domestic product on stock prices in Bursa Malaysia (KLCI). Since 1987 to 2017, data will be collected annually.